Q: Simplify: (x - 8)2
A. x2 + 64
B. x2 - 16x + 64
C. x2 - 64x + 16
D. x2 - 16

A: B. x2 - 16x + 64. (x - 8)2 can be expanded to x2 - 16x + 64.

Expert answered|eturker|Points 2772|

Expert answered|eturker|Points 2772|

Question

Asked 1/1/2013 4:14:12 PM

0 Answers/Comments

Rating

There are no new answers.

Solve the quadratic equation. 2x^2 = 32
A. x = ±4
B. x = 2 and x = 32
C. x = 1 and x = 16
D. x = ±2 **Weegy:**
2x^2 = 32;
x^2 = 32/2;
x^2 = 16;
x = ±4
(More)

Question

Expert Answered

Updated 8/31/2014 6:26:33 PM

0 Answers/Comments

Solve for x: (2x - 4)2 = 1
A. 2, 3
B. 3/2, 5/2
C. 3/2, 3/5
D. 3/2, -5/2
**Weegy:** The answer is A. 2,3. (More)

Question

Expert Answered

Updated 8/1/2014 12:40:07 PM

1 Answer/Comment

(2x - 4)^2 = 1;

4x^2 - 16x + 16 = 1;

4x^2 - 16x + 16 - 1 = 0;

4x^2 - 16x + 15 = 0;

(2x - 3)(2x - 5) = 0;

2x - 3 = 0; 2x = 3; x = 3/2;

2x - 5 = 0; 2x = 5; x = 5/2;

Solutions: x = 3/2 or x = 5/2

4x^2 - 16x + 16 = 1;

4x^2 - 16x + 16 - 1 = 0;

4x^2 - 16x + 15 = 0;

(2x - 3)(2x - 5) = 0;

2x - 3 = 0; 2x = 3; x = 3/2;

2x - 5 = 0; 2x = 5; x = 5/2;

Solutions: x = 3/2 or x = 5/2

Added 8/1/2014 12:40:04 PM

This answer has been confirmed as correct and helpful.

Factor out the greatest common monomial: 25a6 - 10a5 - 40a4
A. 5(5a6 - 2a5 - 8a4)
B. 5a(5a3 - 2a2 - 8a)
C. 5a4(5a2 - 2a - 8)
D. 5a6(5 - 2a-1 - 8a-2)
**Weegy:** A (More)

Question

Expert Answered

Updated 8/31/2014 6:08:09 PM

2 Answers/Comments

Factor out the greatest common monomial: 25a6 - 10a5 - 40a4 is 5a4(5a2 - 2a - 8).

25a6 - 10a5 - 40a4

=5a4(5a2-2a-8).

25a6 - 10a5 - 40a4

=5a4(5a2-2a-8).

Added 8/31/2014 6:08:09 PM

This answer has been confirmed as correct and helpful.

Rated good by andrewpallarca, Confirmed by andrewpallarca [8/31/2014 6:21:08 PM]

Factor the trinomial: 2x^2 + 7x + 3
A. (2x - 1)(2x + 3)
B. (2x + 3)(x + 1)
C. (2x + 1)(x + 3)
D. (2x + 1)(2x + 3)
**Weegy:** 2x^2 + 7x + 3 = (2x + 1)(x + 3) (More)

Question

Expert Answered

Updated 13 days ago|5/9/2018 6:36:38 AM

0 Answers/Comments

Factor the polynomial by grouping: x^2 - 2x + 3x - 6
A. (x - 3)(x + 2)
B. (x - 2)(x + 3)
C. 2(x - 2)(x + 3)
D. x2 + x - 6 **Weegy:** x^2 - 2x + 3x - 6
= (x - 2)(x + 3) (More)

Question

Expert Answered

Updated 6/8/2014 4:34:01 PM

0 Answers/Comments

26,905,835 questions answered

There are no comments.